Effect of NPS Rate on Yield and Yield Components of Upland Rice (Oryza sativa L.) in Western Region of Ethiopia - Guddisa , Bodena; Anbassa, Fufa (International Journal For Research In Agricultural And Food Science, 2019)
The key elements that contributed to low rice productivity is such biotic, abiotic factors and inappropriate crop management practices. Moreover, application of balanced fertilizers is the basis to produce more crop yield from existing land under cultivation and nutrient needs of crops is according to their physiological requirements and expected yields. Thus, a field experiment was conducted in 2016-2018 main cropping season from the end of may to end November at western oromiya on Bako and Chewaka locations to improve soil fertility and increase yield of Rice in East Wollega and West showa and to determine optimum level of NPS fertilizer for growth, economically feasible rates that maximize the yield of Rice in the area. The treatments were factorial combination of seven rates of fertilizer (0, 25, 50, 75, 100, 125 kg/ha NPS) and one previous recommendation (100 kg/ha DAP) with two Rice varieties (chewaka and Nerika-4) and with uniform application 23 N kg/ha in randomized complete block design and replicated three times. The pre soil analysis indicates that the soil of experimental area is acidic (pH = 5.4) and medium in available Phosphorus (13 ppm). The main effect of Plant height, Panicle length and number of effective tiller were not influenced by NPS rate but significantly (P<0.01) different due to variety both at Bako and Chewaka locations. But the main effect of Above ground biomass and Grain yield were significantly different at chewaka site. Though the other parameters were non-significantly affected, Grain yield of chewaka variety was significantly influenced due to the interaction effect of NPS rates and varieties at Bako. Thus, economic analysis revealed that 125 kg/ha NPS (47.5 P2O5, 23.75 N and 8.75 kg/ha S) rate on chewaka variety gave grain yield (6454.8kg/ha) with the net benefit (61160.5 birr/ha) and the highest marginal rate of return (787.69%) are economically feasible alternative to the other treatments. Therefore it is advisable to use 125kg/ha NPS rate on chewaka variety since economically feasible to the farmers.